ANALISIS EFEKTIVITAS PEMBELAJARAN MAHASISWA PADA MATA KULIAH STATISTIK SECARA DARING PADA MASA PANDEMI COVID-19 - Ahmad Taufik (JURNAL ILMIAH GLOBAL EDUCATION, 2022)
This study aims to analyze the effectiveness of student learning in Statistics courses online during the Corona Virus pandemic. This research is a qualitative descriptive study. The number of respondents studied in this study were 27 respondents consisting of active students of Physical education at the Global Nusantara Education Institute. Samples were taken using a saturated sampling technique. Data collection techniques using a questionnaire technique. Data analysis techniques include data reduction, data presentation and drawing conclusions. The conclusion of this study is that there are various kinds of difficulties faced by Physical Education students at the Global Nusantara Education Institute during online learning. The difficulties in the online learning process experienced by students lie in the effectiveness of the teaching and learning process and also technical constraints such as unstable internet networks, limited quotas and minimal interaction when the online learning process takes place.